Young learners’ motivation, self-regulation and performance in personalized learning - Ackermans, Kevin; Bakker, Marjoke; van Loon, Anne-Marieke; Kral, Marijke; Camp, Gino (Computers and education, 2025)
Personalized learning, a topic that has garnered significant attention in education, is known for its potential to cater to student's unique needs and improve educational outcomes. However, most large-scale longitudinal studies on personalized learning have primarily focused on middle school students and above (age ≥11). This study, in contrast, delves into the uncharted territory of how personalized learning affects younger students (ages 7–12), a domain largely overlooked by large-scale studies. To understand the effect of PL on young learners’ academic performance, metacognitive awareness, and motivation. Multidisciplinary design teams embedded personalized learning in eight participating elementary schools, resulting in personalized learning interventions tailored to each school in four subjects. The effects were measured over three years among 588 students and 82 teachers and analyzed using a Bayesian Gaussian regression with random intercept models and nested groups. We found significant evidence that the personalized learning interventions fostered academic performance in two of the four subjects: math and spelling. Regarding spelling, we found that the schools in which metacognitive skills were explicitly trained improved their students' spelling performance significantly compared to other schools. We found significant evidence suggesting that student ICT skills improved metacognitive awareness, intrinsic motivation, and math performance. We also found significant evidence that teachers' ICT skills support student metacognitive awareness. However, we could not confirm the theorized effect of personalized learning on metacognitive awareness or students’ intrinsic motivation. Our study provides evidence-based recommendations for implementing personalized learning interventions in elementary schools, particularly for math and spelling. Finally, improving ICT skills among students and teachers benefits students in math and in their metacognitive skills. •Personalized learning boosted academic performance in math and spelling.•School explicitly training in metacognition improved spelling performance.•Student digital literacy improved metacognition evaluation and intrinsic motivation.•Teacher digital literacy supported student metacognition knowledge.